Pengembangan Buku Bergambar Bertekstur Dilengkapi Teka-Teki Silang Sebagai Media Pembelajaran Biologi Sub Materi Jaringan Epitel Kelas XI SMA - Saifullah Hidayat; Fima Diah Rovvy Anggraeni; Siti Mukhlishoh (Symbiotic: Journal of Biological Education and Science, 2020)
Media is one of tool to help the learning process. The media used in Senior Hight School 7 Semarang still general like book and LKS, the media admitted still has weakness from the presentation of contents, picture and increasing students interest, so that the learning looks monotonic and less to give progress of learning which is fun in the class. The thing explained raises the results of research like Developing The Book Which has Pictures and Textured and It is Completed with Crossword Puzzle As Media Learning Sub Material Materials Epitel Class XI SMA. This research uses the method. (R & D) with 4-D development model Thiagarajan dkk production Defind, Design, Develop and Dessiminate. The result of the research is based on the assessment of media material expert has decent criteria (Very Good) with 90.9% percentage, assessment according to the media expert is included in the criteria worth (excellent) with 85.5% percentage and the assessment according to the teacher is included in the appropriate category (Very Good) with a percentage of 98.48%. The effectiveness of the media on the value of entry in the category is quite effective with the mean of the average student control score of 5.70. Media readability test after using in the learning category is very good with a percentage of 86.1%. The result of reseach showing deserves using in the learning.